Relationships between herbivores and Colophospermum mopane of the Northern Tuli Game Reserve, Botswana - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2022)
Dissertation (MSc (Zoology))--University of Pretoria, 1993.